Physical Environment of Rural School in Conducting Effective Collaborative Learning - Sarwanti, Sri (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Education has undergone tremendous development. The education paradigm has shifted from teacher-centered towards student-centered. In this new paradigm, Brown (2015) states that students have more emphasize and participation in the teaching learning process. Collaborative learning is an umbrella term for a variety of approaches in education that involve joint intellectual effort by students or students and teachers. Collaborative learning refers to methodologies and environments in which learners engage in a common task in which each individual depends on and is accountable to each other. Unesco (2017) states that learning takes place in multiple settings and the learning environment can be structured or unstructured and the learning in different environments can complement each other. Formal and non-formal education occurs mainly in structured environments in the form of institutions (schools, community centers, multimedia centers, learning villages/cities, etc.). The learning environment in the classroom is vital to studentsâ success and impacts them in many ways. This study reveals the physical environment of rural school in conducting the teaching and learning process. The data are collected by using observation and questionnaire. The study is qualitative exploratory. The results of this study show genuine data of the condition of physical environment in rural school. The results would be an input for researchers or decision makers who are keen on rural development.